PdP/WO3 multi-functional catalyst with high activity and stability for direct liquid fuel cells (DLFCs). Issue 18 (27th August 2021) - Kumar, Sachin; Soni, Roby; Kurungot, Sreekumar
Abstract : An electrocatalyst comprising PdP nanoparticles anchored over WO3 nanorods (PdP/WO3 ) was prepared, which acts as a carbon-free system with multi-functional activity for ORR, MOR, and FOR in Direct Liquid Fuel Cells (DLFCs). Abstract : Direct liquid fuel cells are energy conversion devices which utilize formate and methanol as fuels. These systems are relieved of the problem of H2 transport and storage, making them highly desirable for various practical applications. However, the low stability and activity of carbon supported catalysts such as Pt/C both in the anode and cathode is a critical hindering factor towards their further development. As a practical solution to overcome this issue, in this work, we report on the development of phosphorus-doped palladium (PdP) nanoparticle-supported tungsten oxide (WO3 ) nanorods (PdP/WO3 ) as a versatile multifunctional catalyst for facilitating the oxidation of formate and methanol in the anode and the oxygen reduction reaction (ORR) in the cathode. Strong metal–support interactions and electronic modifications incurred by the doped phosphorus help this system to achieve desirable properties to enable it to effectively function both for the anode and cathode applications. PdP/WO3 showed 16-times higher mass activity compared to Pt/C even after 3000 start/stop cycles for the ORR. For formate and methanol oxidation, PdP/WO3 exhibited current densities of 0.50 and 0.734 A mgPd −1, respectively, outperforming the state-of-the-art catalysts. With these bifunctional features, PdP/WO3 stands out as a potential system to be used as an anode and cathode catalyst in direct liquid fuel cells, all the while offering an opportunity for the development of carbon-free electrocatalysts.